ISSUES OF DEPRECIATION AND FREE TRANSFER OF FIXED ASSETS IN AGRICULTURAL ENTERPRISES - Xojimurodov Zuxriddin (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the write-off and gratuitous transfer of fixed assets in agricultural enterprises. It examines the definition and approaches of economists and industry experts to the concept of fixed assets. Conclusions are drawn and recommendations are offered for the write-off and gratuitous transfer of fixed assets.